The politics of religion and the rise of social Catholicism in Peru (1884-1935) - Cubas Ramacciotti, Ricardo. (Religion in the Americas, 2017)
In The Politics of Religion and the Rise of Social Catholicism in Peru (1884-1935) Ricardo Cubas Ramacciotti provides a lucid synthesis of the Catholic Church's responses to the secularisation of the State and society whilst offering a fresh appraisal of the emergence of Social Catholicism and its contribution to social thought and development of civil society in post-independence Peru. Making use of diverse historical sources, Cubas provides a comprehensive view of a reformist yet anti-revolutionary trend within the Peruvian Church that, decades before the emergence of Liberation Theology and under divergent intellectual paradigms, developed an active agenda that addressed the new social problems of the country, including those of urban workers, and of indigenous populations.